Apakah pengumuman resmi kasus pertama Covid-19 oleh Presiden Joko Widodo memiliki kandungan informasi? Event study pada saham-saham LQ-45 - William Wendy Ary (Universitas Widya Mataram, 2021)
This study analyzes the phenomenon of the first case of Covid-19 transmission in Indonesia and its impact on the capital market in Indonesia. This study aims to test whether there is a negative PCAD pattern after the first announcement of the covid-19 virus transmission case on the Indonesian capital market and to prove that the Indonesian capital market experienced a significant decline in returns after the first announcement period of the covid-19 virus transmission. Stocks that are included as LQ45 stocks are being utilized and event study is the method to analyze the market response during the window period (t-10, t+10) and uses the independent sample t-test to compare the average abnormal return. mean (AAR) and mean cumulative abnormal return (CAAR). The results of this study indicate that the market takes a wait & see strategy, PCAD shows the form of a negative sign after the event and there is a difference between AAR and CAAR 10-days before and 10-days after the event. Overall, this research shows that the market has responded negatively to information related to the Covid-19 virus.